PENGARUH MODEL PEMBELAJARAN COOPERATIVE TIPE SCRIPT DENGAN PENDEKATAN INQUIRI TERHADAP HASIL BELAJAR BIOLOGI SISWA SMP - Sella Wamir; Eka Apriyanti; St. Humaerah Syarif (Ikatan Keluarga Alumni FKIP Universitas Tanjungpura, 2023)
This study aims to determine the effect of the script-type cooperative learning model with an inquiry approach on students' biology learning outcomes in the circulation system material of Marlasi 4th Public Middle School. This research is a quasi-experimental research. The design used was a pretest-posttest control group with two different treatment groups. The experimental group used a script type cooperative learning model with an inquiry approach, while the control group used a direct learning model. Based on the results of testing the hypothesis using the t test, the value of tcount = 4.045 is greater than the value of ttable = 2.101 with a significance level of 0.05. In addition, it can be seen from the results of the post-test calculations for the experimental class using the script-type cooperative learning model with the inquiry approach (mean value = 82.6) showing a higher score than the control group's post-test using the direct learning model (mean value = 75.8), so it can be concluded that the use of the Script Type Cooperative Learning Model with an Inquiry Approach has an effect on Student Biology Learning Outcomes on Circulation System Materials at SMP Negeri 4 Marlasi. This learning model can be an alternative used by biology teachers in carrying out learning activities in the classroom to improve students' biology learning outcomes, while still paying attention to the subjects that are relevant to this learning model